CHALLENGES OF NEURODIDACTICS IN COLOMBIAN INCLUSIVE EDUCATION MEDIATED BY TECHNOLOGICAL ADVANCES - Diana Mayerli Antolínez Buitrago (DIALÉCTICA, 2026)
Education has recently faced significant changes that converge in the search for new ways of teaching using technology, which has now largely permeated teaching and learning processes. This leads us to take a look at elements that are being used in the educational environment and that need to be taken into account in today's education. From this theoretical standpoint arises the present general objective: to reflect on the challenges of neurodidactics in inclusive education, mediated by technological advances in Colombian education. The methodology is framed within an analysis based on the principles of qualitative research through the interpretive paradigm supported by the qualitative approach centered on the hermeneutic method backed by the technique of documentary analysis, which generated this argumentative essay that seeks to make a significant contribution so that teachers adopt some principles of neurodidactics to promote quality education, based on the application of technological advances that enrich the teaching and learning process and, at the same time, strengthen inclusive education, which has now become an essential issue for education in general.